Peningkatan Mutu Layanan di Kampung Homestay Borobudur Melalui Pembelajaran Bahasa Prancis - Sajarwa Sajarwa; Aprilia Firmonasari; Wulan Tri Astuti (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
Community engagement, in tri dharma, is a dharma that is directly related to society. Department of French Literature, Faculty of Cultural Sciences, Universitas Gadjah Mada carry out a community engagement program by conducting a French language training for employees in Kampung Homestay, Dusun Ngaran II, Borobudur Village. Tis training is delivered by tutorial system using communicative method. Expected result of this training is that the homestay employees can communicate in French with simple structures and phrases. In addition, Department of French Literature also helps the homestay to promote itself through a website or brochure in French, so that French-speaking foreign tourists can get to know this village better. Tis activity also produces teaching materials and videos of French-language tourism based on local cultures.